ANALISIS ASPHALT WEARING COURSE (AC-WC) DENGAN BAHAN TAMBAH LIMBAH KAIN POLYESTER AND RESIN POLYESTER PADA PERKERASAN JALAN - SITI NURHAFIDZA AKHMAD; Putri Inna Wahidiyati; Juny Andry Sulistyo (UNISSULA Semarang, 2025)
ABSTRACT Asphalt Concrete Wearing Course (AC-WC) is the top layer of flexible pavement that directly receives traffic loads and is exposed to extreme weather. The quality of AC-WC is greatly influenced by its mechanical properties and durability. This research aims to analyze the effect of adding polyester fabric waste and polyester resin on the characteristics of the AC-WC mixture. Polyester fabric waste was chosen because it has good tensile strength, wear resistance, and physical properties, while polyester resin is used to increase the adhesion and stability of the mixture. The research was conducted experimentally in a laboratory with variations in the percentage of polyester fabric and polyester resin added. Test specimens were made according to the 2018 General Specifications of Bina Marga and tested using the Marshall method. Parameters measured include stability, flow, Marshall Quotient (MQ), Void in Mix (VIM), and other supporting parameters. The test results show that the addition of polyester fabric waste and polyester resin at certain levels can increase stability and MQ values, and improve the mixture's resistance to plastic deformation and cracking. In conclusion, the utilization of polyester fabric waste combined with polyester resin has the potential to be an environmentally friendly additive alternative to improve the performance of AC-WC, while reducing the negative impact of textile waste on the environment. Keywords: AC-WC, polyester fabric waste, polyester resin, Marshall test, road pavement.